Isometrias e homotetias: teoria e aplicações com o GeoGebra e materiais manipulativos - Bertó, Marcelo Luiz (2021)
This work comprises a bibliographical research in books and scientific articles dealing with the theme geometric transformations isometry - reflection, translation and rotation - and homothety. It has for aim to present a study on these themes, showing definitions and properties, as well as the use of these concepts in solving geometric problems, especially geometric constructions. In this work, the GeoGebra software was used to construct the figures and it is also made a report detailing how some problems of geometric constructions were solved with the help of this software. Finally, activities with manipulable materials are presented, like for example folding, involving the theme geometric transformations that can be used in classroom with elementary school students. It is hoped that this work can serve as a source of research on issues involving the topics mentioned, focusing mainly on student motivation, teaching and learning with the possible use of technologies digital, allowing the student to interpret, to experiment, to visualize, to conjecture and to generalize in the perspective of a more pleasant and inspiring learning.